Don't Leave Me Hanging on the Anglophone: The Potential for Online Distance Higher Education in the Asia-Pacific Region - Simon Marginson, Monash University, Australia (Higher Education Quarterly, 0951-5224 Volume 58, Nos. 2/3, April/July 2004, pp 74-113, 2004)
In the last decade there have been many attempts to mount online distance higher education programs on a global scale, led by the e-learning industry and university companies and consortia, some with government support: e.g. Universitas21 Global, Cardean University, Fathom, NYUOnline and the UKe-University. A primary commercial objective has been student markets in the Asia-Pacific nations, especially China, given unmet domestic demand and the growth of cross-border education. However while for-profit providers such as the University of Phoenix Online have shown mass online programs are viable in targeted markets, albeit more expensive than face-to-face programs, would-be global ventures have faltered or collapsed. The paper reviews the failure of English language global e-learning in the light of industry marketing strategies, the economics of online education, and the specifics of Asia-Pacific nations including unmet demand for education. It argues that for exporter universities, the potential of cross-border online education can only be realised if communications capacity in the Asia-Pacific nations is enhanced; and online programs are teaching-intensive, and customised for cultural and linguistic variations. Long-term equal partnerships with local and system providers are essential. For policy makers, the implosion of global e-learning points to the need to use expert judgment in relation to the different options for enhancing the capacity of higher education at home and abroad. It also suggests the need for greater scepticism about commercially driven scenarios and claims of company prospectuses, and about the viability of market-controlled paths of development.